Assessing Materiality in Sustainability Reporting and the Role of MSMEs - Srinivasan Ragothaman (Lembaga Penerbit Fakultas Ekonomi dan Bisnis Universitas Trisakti, 2023)
This paper is about the materiality concepts in financial reporting and sustainability. The term materiality refers to those issues that can have significant repercussions on the company and society. Big corporations readily disclose their environmental practices hoping to drive business growth and micro, small, and medium enterprises (MSMEs) which are a big part of the Indian economy and they contribute roughly 30 percent of the nation’s GDP also strive to implement good environmental practices and the This chapter discusses materiality definitions and guidelines issued by GRI, SASB, and IIRC regarding material disclosures in sustainability reports. It enumerates the process of assessing materiality and provides examples of the materiality matrix. It summarizes prior research and also provides some statistics from the Ministry of MSME in India and other sources.